1999
DOI: 10.1093/clinchem/45.7.1018
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Cardiac Troponin I in Serum Complicates Comparisons of Cardiac Troponin I Assays

Abstract: Background: Up to a 20-fold variation in serum cardiac troponin I (cTnI) concentration may be observed for a given patient sample with different analytical methods. Because more limited variation is seen for control materials and for purified cTnI, we explored the possibility that cTnI was present in altered forms in serum. Methods: We used four recombinantly engineered cTnI fragments to study the regions of cTnI recognized by the Stratus®, Opus®, and ACCESS® immunoassays. The stability of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…The healthy control animals in this study had cTnI concentrations comparable to those of healthy animals reported in other studies . Although results of different assays cannot be directly compared, many studies using different cTnI assays report similar values for healthy animals, whereas the assays differ considerably (up to 20‐fold) in the higher concentration ranges . As release of higher concentrations of cTnI invariably also leads to a higher proportion of circulating modified cTnI, it has been speculated that some assays perform better at detecting modified forms than others.…”
Section: Discussionsupporting
confidence: 66%
“…The healthy control animals in this study had cTnI concentrations comparable to those of healthy animals reported in other studies . Although results of different assays cannot be directly compared, many studies using different cTnI assays report similar values for healthy animals, whereas the assays differ considerably (up to 20‐fold) in the higher concentration ranges . As release of higher concentrations of cTnI invariably also leads to a higher proportion of circulating modified cTnI, it has been speculated that some assays perform better at detecting modified forms than others.…”
Section: Discussionsupporting
confidence: 66%
“…[17][18][19] The use of purified complexed cTnI (to cardiac troponin T or C) might have been useful in this study; however, similar differences in analytical methods between purified cTnI and patient cTnI values have been noted in human medicine. 20 Although the lack of a common calibrator among analyzers may be a major reason for the large differences in results seen both in this study and in human studies, other factors may be at play. Additional explanations for the differences among analyzers as well as the differences among purified samples and clinical samples include different target amino acids for each analyzer, the variable complexed or noncomplexed forms of cTnI recognized by the antibodies in each assay, and modification (degradation or phosphorylation) of circulating cTnI after myocardial injury that variably influences the detection of cTnI by different analyzers.…”
Section: Discussionmentioning
confidence: 69%
“…Additional explanations for the differences among analyzers as well as the differences among purified samples and clinical samples include different target amino acids for each analyzer, the variable complexed or noncomplexed forms of cTnI recognized by the antibodies in each assay, and modification (degradation or phosphorylation) of circulating cTnI after myocardial injury that variably influences the detection of cTnI by different analyzers. 1,19,20 This latter point may explain why the fold differences among analyzers were greater at higher cTnI concentrations; perhaps the Access is better able to detect modified forms of cTnI after cardiac injury than the Biosite and Stratus. Such cTnI modifications have been shown in rat models and in human beings; however, this hypothesis has not been investigated in dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45,46 Variations in the measured cTnI concentration occur when the same samples are analyzed with different immunoassays. 46 The absolute measured cTnI concentration is not comparable among different assays. Therefore, the results of this study are only valid for measurement of bovine serum cTnI concentrations with the i-STAT immunoassay and cannot be compared to other immunoassays.…”
Section: Discussionmentioning
confidence: 99%